Born of the Same Roots Stories of Modern Chinese Women - Hsu, Vivian Ling (Indiana University Press, 1981)
The problems, struggles, and triumphs of twentieth-century Chinese women are the subject of the nineteen short stories of this anthology. Spanning over fifty years of Chinese history, these works reflect a period of tumultuous upheaval, national division, and radical social change. The contemporary writers represented, both the prominent and the little known, come from the People's Republic of China and from Taiwan; a few are immigrants to the United States. All the stories focus on the personal and social aspects of women's lives, without imposing solutions to the negative situations exposed. Those stories written in the PRC (where the Communist regime's control over literature has been absolute) are perhaps an exception to the rule, since they do not so much depict reality as hold up for emulation a model of ideal behavior.